Proportionality of Clinical Outcome and Placental Changes to the Increasing Severity of Maternal Hypertension- An Observational Study - Priyadharshini BARGUNAM; Parvathi JIGALUR; Purushotham REDDY (Federation of Turkish Pathology Societies, 2023)
Objective: Preeclampsia and eclampsia remain the major causes of maternal and perinatal mortality and morbidity worldwide, causing 1215% of direct maternal deaths. Although preeclampsia and related hypertensive disorders of pregnancy continue to affect 8% of all pregnancies, the incidence of preeclampsia has increased 40% in recent years. This study was carried out to analyse the different placental lesions and fetal outcome in different grades of maternal hypertension and to see if there is a linear relationship of the same. Material and Method: A total of 539 placenta specimens received at the department of Pathology from October 2017 to March 2019 were collected after obtaining informed consent. Of the 539 placentas, 87 hypertensive cases were graded and grouped according to the severity as gestational hypertension, mild preeclampsia, severe preeclampsia, eclampsia, and chronic hypertension and compared with 88 normotensive cases. The gross and microscopic findings were tabulated and analysed using the Statistical Package for the Social Sciences (SPSS) software. Results: Incidence of fetal death and growth restriction increased with increasing grade of maternal hypertension (p= 0.001). Abnormal shape of placenta (p= 0.034) and abnormal umbilical cord insertion (p= 0.028) were seen significantly more in the hypertensive group than in the normotensive group. Infarct and abnormal vasculo-syncytial membrane (p< 0.05) and abnormal villous maturation (p= 0. 039) were significantly increased in the hypertensive group than the normotensive group. Conclusion: The incidence of adverse fetal outcome and placental changes suggestive of feto-maternal malperfusions shows a proportional trend with the increasing grade of maternal hypertension.